DETEKSI SPORA DI UDARA PADA PERMACULTURE AREA DI BUKIT KOR TERENGGANU MALAYSIA - Rizkina, Setia Azzahra; Fitria, Fitria; Suprianto, Andi Agus; Mohamed Sidique, Siti Nordahliawate (Fakultas Pertanian, Universitas Janabadra, 2024)
Permaculture is closely related to sustainable, continuous and permanent life. Therefore, permaculture has the principle of balance and sustainability. The growth of microbes or spores can be detrimental to plants even if the ecosystem and environment are healthy and good, such as a permaculture area. The spread of plant diseases is often caused by spores spread through the air. The aim of this research is to determine the distribution of spores in the air in the Kor Hill permaculture area. Observations of spore samples were carried out in September 2023 at the Kor Hill Agricultural Complex laboratory, Marang, Terengganu, Malaysia at a height of 35 meters above sea level. This research used the Completely Randomized Design (CRD) method. The research results showed that the spore colony samples observed were groups of fungi known as sterile hyphae or sterile mycelia. Sterile hyphae or sterile mycelia are a type of fungus that does not produce reproductive structures, either through sexual or asexual reproduction.Keywords: Permaculture, spores, sterile myceliaINTISARIPermakultur sangat erat kaitannya dengan kehidupan yang lestari, terus menerus, dan permanen. Maka dari itu, permakultur memiliki prinip keseimbangan dan berkelanjutan. Pertumbuhan mikroba atau spora dapat merugikan tanaman meskipun ekosisten dan lingkungannya sehat dan baik seperti area permakultur. Penyebaran penyakit tanaman seringkali disebabkan oleh spora yang tersebar melalui udara. Tujuan penelitian ini adalah untuk mengetahui persebaran spora di udara pada area permakultur bukit Kor Pengamatan sampel spora dilakukan pada bulan September 2023 di laboraturium Komplek Pertanian Bukit Kor, Marang, Terengganu, Malaysia dengan ketinggian 35 meter diatas permukaan laut. Penelitian ini menggunakan metode Rancangan Acak Lengkap (RAL). Hasil penelitian menunjukkan sampel koloni spora yang diamati berupa kelompok jamur yang disebut sebagai hifa steril atau miselia steril. Hifa steril atau miselia steril merupakan jenis jamur yang tidak menghasilkan struktur reproduksi, baik itu melalui reproduksi seksual maupun aseksual. Kata kunci: permakultur, spora, miselia steril